2014
DOI: 10.1111/pin.12232
|View full text |Cite
|
Sign up to set email alerts
|

Acquired cystic disease‐associated renal cell carcinoma with a focal sarcomatoid component: Report of a case showing more pronounced polysomy of chromosomes 3 and 16 in the sarcomatoid component

Abstract: Acquired cystic disease (ACD)-associated renal cell carcinoma (RCC) has recently been established. Herein we report the sixth case of ACD-associated RCC with a sarcomatoid change. The patient was a 77-year-old man who regularly underwent hemodialysis for 14 years due to chronic renal failure resulting from IgA nephropathy. On computed tomography, a large right RCC was observed with contrast enhancement in the arterial phase. A nodular protrusion into the perirenal fat was detected. Right nephrectomy was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The presence of multiple renal cysts and close association of these specific cyst types with ACD-RCCs suggest a sequential progression from cyst to carcinoma. 12,13 Similarly, atypical cysts lined by cells with eosinophilic cytoplasm and large nucleoli were always found in association with ACD-RCC. 11 The presence of atypical cysts and oxalate deposition is significantly greater in ACD-RCC compared with CCRCC and is believed to be related to the longer duration of dialysis occurring with ACD-RCC.…”
Section: Clinical Featuresmentioning
confidence: 95%
See 4 more Smart Citations
“…The presence of multiple renal cysts and close association of these specific cyst types with ACD-RCCs suggest a sequential progression from cyst to carcinoma. 12,13 Similarly, atypical cysts lined by cells with eosinophilic cytoplasm and large nucleoli were always found in association with ACD-RCC. 11 The presence of atypical cysts and oxalate deposition is significantly greater in ACD-RCC compared with CCRCC and is believed to be related to the longer duration of dialysis occurring with ACD-RCC.…”
Section: Clinical Featuresmentioning
confidence: 95%
“…2,11 Isoform characterization of cadherin by immunohistochemistry has also shown that ACD-RCC cells are derived from proximal tubules that express N-cadherin but lack E-cadherin, a marker of distal tubule differentiation. 11,12 It has been suggested that the proximal tubule phenotype may contribute to the deposition of calcium oxalate crystals that are characteristic of ACD-RCC. 2 The pathophysiologic mechanisms underlying epithelial hyperplasia and tumorigenesis of ACD-RCC are still under investigation.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations